The Jahai Negritos at Sungai Rual resettlement, Kelantan: A brief study on the social organisation of a tribal community in Malaysia with special emphasis on their institutions of marriage / Abd Rashid Idris - Abd Rashid, Idris (1976)
The Jahai population discussed in this report are residing in a resettlement established by JHEOA in 1972 with the sole purpose of regrouping into one location the whole population of the once nomadic Jahai from the jungles at the north-eastern part of Malaysia peninsular. This resettlement is situated at the easter part of kelantan state, not very far away from the border of the state of perak, and only a few miles away from the Thai border to the north. This settlement is know as Sungai Rual resettlement, and the name is after the name of a small but panaramic mauntain stream that flows through the site. JHEOA coded this settlement as Sungai Rual post. This settlement together with settlements for other orang asli tribes through put the country were set up with the main objective of containing such people so as to make ir easier and more effective for the government in carrying out it's material and mental development programs for the orang asli. This objective is in fact have become the goverment policy towards the orang asli since independence.